A global view of hepatopancreas and intestinal reveals the potential influencing mechanism of aflatoxin B1 on nutrition and metabolism in Litopenaeus vannamei. (12th August 2019) - Wang, Yilong; Liu, Mei; Wang, Baojie; Jiang, Keyong; Wang, Mengqiang; Wang, Lei
Abstract: The present study was to determine the time‐dependent alterations in growth performance, histomorphology, digestive enzymes activities and the genes expression related to target of rapamycin (TOR) signalling pathway involved in hepatopancreas and intestine of Litopenaeus vannamei at 3, 6, 12, 18, 24 and 30 days after Aflatoxin B1 (AFB1) challenge. The results manifested that AFB1 could induce a significant decrease in growth performance and visible variations of the hepatopancreas and intestine structures in shrimp. Meanwhile, the digestive enzymes activities and genes expression level were significantly lower in the experimental group than in the control group and showed a time‐dependent decrease ( p < 0.05). The expression levels of tor and s6k were significantly higher in the experimental group than in the control group from days 6 to 24 and showed a tendency to increase first and then decrease as a whole ( p < 0.05). Meanwhile, we analysed candidate pathways involved in hepatopancreas and intestine of shrimp in metabolic response to AFB1. The mainly disturbed pathways related to metabolism in hepatopancreas were involved in pyrimidine, glycosylphosphatidylinositol, glycosaminoglycan, vitamin and amino acid biosynthesis and metabolism, while the mainly disturbed metabolic pathways in intestine were glycosaminoglycan, vitamin and amino acid biosynthesis and metabolism.